„Ile zwierząt zabrał Mojżesz do swojej arki?” Zwierzęce, dziecięce i poetyckie według Justyny Bargielskiej - Nawarecki, Aleksander (Zoophilologica. Polish Journal of Animal Studies, 2015)
The text is an interpretation of a poem by Justyna Bargielska titled Katullka from the Nudelman (2014) volume. The author uses the literary idea of meeting herself from many years before. The occasion was her discovery of her own childish notes showing her knowledge about the world in the form of three riddles. The most difficult and most important of them (“How many animals did Moses take onto the Ark”?) is based on the mixing of two expressions: “Noah’s Ark” and “the Ark of the Covenant” (Moses’). The deceptive question of the child forces us to seek animals in the Bible (especially in the Decalogue), which leads to surprising theological conclusions concerning relations with God and animals. In the finale of the poem, the writing of the seven-year-old girl is eaten by a roe deer; this is a symbolic suggestion of a “communion” between the child-like and the animal-like.